Evaluación de la calidad de la lana en ovinos Marin Magellan Meat Merino (4m) en la sierra centro del Ecuador - Beltrán Romero, Cristian Fernando (2022)
The objective of the research is to contribute to the study of the quality of the wool, because after meat production it is the transcendental factor of production, it is important to know the characteristics of the wool of the sheep of the Mestiza breed offspring of the 4M and compare them with pure 4M sheep imported from Chile. The wool samples were characterized and compared by applying the quantitative and qualitative descriptive statistical method with the analysis of variance, T student with the following results, that for the fineness diameter of the wool, in crossbred sheep offspring of 4M there is a mean of 24.93±0.76 μm taking into account the lower limit 22.8 and an upper limit 27.06; the mean length of the wick is 84.69 ± 8.32; with a lower limit of 82.56 and an upper limit of 86.82, and the average crimpness is 4.5±0.45 with a lower limit of 2.37 and an upper limit of 6.63, obtaining a statistical difference of value < 0.0001. For the qualitative lanimetric variables: Point of Break (POB) it is identified that 9 animals are in a medium characteristic and 6 in low.